INTEGRATION OF TECHNOLOGY IN ISLAMIC BOARDING SCHOOLS CURRICULUM IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW ON INTEGRATIVE CURRICULUM MODELS AND INNOVATIONS IN LEARNING - Arbain Nurdin; Saiful Anwar; Akhsanul In’am; Faridi; Moh. Nurhakim (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The purpose of this study is to describe the integrative curriculum model in Islamic Boarding Schools in Indonesia and to describe learning innovations by integrating technology in Islamic Boarding Schools in Indonesia. The design of this research is a systematic literature review of accredited articles starting from 2019-2025. The article is sourced from DOAJ, google scholar and scopus. The data was analyzed using descriptive analysis techniques. The researcher found 156 articles, then selected with a coding model using the Nvivo application, in the final stage 28 articles were found that were relevant to the TAPUPAS criteria and research questions. Based on the descriptive analysis, it was found that, first: the integrative curriculum model in Islamic boarding schools in Indonesia can be classified into two aspects, namely the integrative curriculum design aspect between the national curriculum and the Islamic Boarding School curriculum or the international curriculum. The implementation aspects include learning activities, materials, approaches and methods, as well as learning evaluation. The second research finding is forms of learning innovation by integrating technology in Islamic Boarding Schools in Indonesia in the form of the use of digital media and technology-based learning methods. Meanwhile, the implications for the effectiveness and quality of learning.